Peningkatan Hasil Belajar Siswa Pada Pembelajaran IPS Menggunakan Model Cooperative Group Investigation di Kelas V SD - Nefira, Laonny Lafebra; Nasrul, Nasrul; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was improve the students achievement in learning social science used coopeative group investigation of 5th grade elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were students of 5th grade were 25 people consist of 10 men and 15 women. Research conducted in two cycles with research procedure includes of planning, implementation, observation, and reflection. The result of research was improve a) Lesson plan the cycles of I was 76,78% and the cycles II of 92,86% b) Implementation teacher’s activity of I cycle was 79,69% and II cycle was 93,75% while implementation students activity of I cycle was 75% and II cycle was 93,75% c) the students learning outcomes in the I cycle was 76,18 and II cycle was 87,20. It can be concluded that used cooperative learning type GI can improve students achievement in learning social science of 5th grade at SDN 18 Air Tawar Padang.Keyword : Learning outcomes, Social science, GI